An affordable, adaptable, and hybrid assistive device for upper-limb neurorehabilitation. (November 2016) - Malosio, Matteo; Caimmi, Marco; Cotti Cottini, Michele; Crema, Andrea; Dinon, Tito; Mihelj, Matjaz; Molinari Tosatti, Lorenzo; Podobnik, Janez; Prini, Alessio; Seneci, Carlo; Spagnuolo, Giulio
The paper presents a multisensory and multimodal device for neuromuscular rehabilitation of the upper limb, designed to enable enriched rehabilitation treatment in both clinical and home environments. Originating from an existing low-cost, variable-stiffness rehabilitation device, it expands its functionalities by integrating additional modules in order to augment application scenarios and applicable clinical techniques. The newly developed system focuses on the integration of a wearable neuromuscular electrical stimulation system, a virtual rehabilitation scenario, a low-cost unobtrusive sensory system and a patient model for adapting training task parameters. It also monitors the user behavior during each single session and its evolution throughout the entire training period. The result is a modular, integrated and affordable rehabilitation device, enabling a biomechanical, neurological, and physiological-based training of patients, including innovative features currently unavailable within off-the-shelf rehabilitation devices.